الوقف الصحي صوره وتطبيقاته المعاصرة - ببوخة نهلة (University of Eloued جامعة الوادي, 2024)
"تناولت هذه الدراسة موضوع الوقف الصحي صوره وتطبيقاته المعاصرة، ودارت محاورها حول الإشكالية الرئيسية وهي: ما مدى مشروعية الوقف الصحي؟ وما هي صوره وتطبيقاته المعاصرة؟ وتم تحليلها من خلال ثلاثة مباحث، كان الأول حول ماهية الوقف الصحي ومشروعيته ومقاصده. أما المبحث الثاني فدرسنا فيه بعض الصور المعاصرة للوقف الصحي واخترنا الصناديق والصكوك الوقفية، وقف الوقت، ومنصات التمويل الجماعي الوقفية، أما المبحث الأخير فتضمن نماذج تطبيقية لهذه الصور (صندوق الوقف الصحي السعودي، وصندوق إنماء، منصة تطوع في وقف الوقت، ومنصتي شفاء واحسان). وقد خلصت الدراسة إلى جملة من النتائج أبرزها: أن مشروعية الوقف الصحي تستمدّ أُسُسها من مشروعية الوقف العام لأنه فرع منه، وتُسري عليه نفس الأحكام والشروط. ويمكن أن تساهم صور الاكتتاب العام والتكتولوجيا في تنمية وتمويل الوقف الصحي. وأوصت الدراسة بدعوة الباحثيين والقانونيين إلى الاهتمام بهذا الموضوع. This study addressed the topic of contemporary charitable endowment (waqf) in theory and practice. It focused on its main problematic، namely: What is the ruling on charitable endowment and what are its modern forms and applications? The study analyzed these questions through three chapters. The first chapter discussed the nature، legitimacy، and objectives of charitable endowment. The second chapter examined contemporary forms such as endowment funds، sukuk (Islamic bonds) and endowments، timing، and crowdfunding platforms. The final chapter included practical examples of the studied forms. The study concluded several findings، notably: The legitimacy of charitable endowment is derived from the general legitimacy of endowment، applying the same rules and conditions. Public offerings and technology can contribute to the development and financing of charitable endowment. The study recommended that researchers and legal experts pay attention to this subject.
Keywords: الوقف، الرعاية الصحية، الوقف الصحي.; Endowment; Health care; Health endowment